2022
DOI: 10.3389/fphar.2022.958146
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of different DNA methyltransferases in the pathogenesis of cancer

Abstract: DNA methylation is one of the most essential epigenetic mechanisms to regulate gene expression. DNA methyltransferases (DNMTs) play a vital role in DNA methylation in the genome. In mammals, DNMTs act with some elements to regulate the dynamic DNA methylation patterns of embryonic and adult cells. Conversely, the aberrant function of DNMTs is frequently the hallmark in judging cancer, including total hypomethylation and partial hypermethylation of tumor suppressor genes (TSGs), which improve the malignancy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 143 publications
1
8
0
Order By: Relevance
“…So it plays an important role in the regulation of the expression of PD-L1 in the TCs [ 38 , 39 ]. Higher PD-L1 expression in dMMR endometrial tumors supports the clinical efficacy of PD-L1 inhibitors in the treatment of solid tumors, with significantly better objective response rates and disease control rates [ 40 ]. Moreover, PD-L1 expression elevated with an increase in TIL abundance within the endometrial tumor microenvironment, suggesting that PD-1 inhibitors could trigger a potent anti-tumor immune response due to the high PD-L1 expression [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 96%
“…So it plays an important role in the regulation of the expression of PD-L1 in the TCs [ 38 , 39 ]. Higher PD-L1 expression in dMMR endometrial tumors supports the clinical efficacy of PD-L1 inhibitors in the treatment of solid tumors, with significantly better objective response rates and disease control rates [ 40 ]. Moreover, PD-L1 expression elevated with an increase in TIL abundance within the endometrial tumor microenvironment, suggesting that PD-1 inhibitors could trigger a potent anti-tumor immune response due to the high PD-L1 expression [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 96%
“…The most well‐known biochemical function of DNMT3A is to catalyze DNA methylation, resulting in the silencing of genes including CDH1. [ 7 , 19 ] However, the silencing of CDH1 expression by DNMT3A, how DNMT3A recognizes CGI on the CDH1 promoter, and whether this is specific to the methyltransferase activity of DNMT3A lack direct evidence. Here, we provide evidence supporting the catalytic‐activity‐dependent role of DNMT3A in driving GBC metastasis, which is strongly correlated with DNA methylation‐mediated CDH1 transcriptional silencing, as verified by the introduction of a catalytically disabled mutation into DNMT3A.…”
Section: Discussionmentioning
confidence: 99%
“…DNMT3A, with its methyltransferase activity, is required for tumorigenesis and the progression of various cancer types. [ 7 ] Previously, we reported that DNMT3A could catalyze DNA methylation within the promoter regions of the elongator complex subunits to generate chemoresistance in GBC and could also be a therapeutic target to sensitize GBC to gemcitabine therapy, [ 8 ] but its role in driving the metastasis of GBC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that DNMTs expression is upregulated in various malignancies (colon, prostate, breast, liver, leukemia) [45,46] and that their expression is associated with aggressive pathologic characteristics [46,47]. Results regarding the expression of DNMTs in ovarian tumors in the literature are equivocal.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation of DNMTs with prognosis is ambiguous and seems to be cancer specific. Some studies have shown that DNMTs levels are associated with an ominous prognosis [47], while others have found that the expression of these molecules, in particular DNMT3A, is associated with good prognosis [27,47]. Regarding ovarian carcinoma, the literature regarding the prognostic role of DNMTs expression is rather sparse.…”
Section: Discussionmentioning
confidence: 99%